Translation Shifts in the Social Dilemma Documentary Movie Subtitle - Hadena Adipta; Ika Kartika Amilia (International Journal of English and Applied Linguistics (IJEAL), 2022)
This study was intended to investigate the types of translation shifts in a documentary movie entitled The Social Dilemma. The method employed was descriptive qualitative to describe the translation shifts occurring in English-Indonesian movie subtitles. The types of shifts were analyzed using Catford's shift typologies. The findings showed that all types of Catford's shifts were applied in the movie subtitles. From the data collected, it was found that there were 56 level shifts (5%), 327 intra-systems shifts (30%), 243 unit shifts (22%), 83 class shifts (7%), and 392 structure shifts (36%). Based on the findings, the type of shift applied the most was structure shift. This happened since English and Indonesian have different grammatical structures, resulting in obligatory and optional shifts. In the obligatory shifts, the form of the SL sentences must be altered following the rules accepted in the TL culture. On the other hand, the SL form can be retained as long as it is still comprehensible in the TL.